2009
DOI: 10.1354/vp.08-vp-0012-v-bc
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Intracerebral Plasmacytoma in a Dog: Microscopic, Immunohistochemical, and Molecular Features

Abstract: A primary intracerebral plasmacytoma was identified in a 7-year-old spayed female Boston Terrier. Grossly, a well-demarcated, 2 cm in diameter, roughly spherical tumor was in the rostral aspect of the left cerebral hemisphere. Histologically, the neoplasm was composed of sheets of round cells with distinct plasmacytoid features and marked anisocytosis and anisokaryosis. Cells were positive for vimentin, CD18, CD79a, and lambda light-chain, and negative for kappa light chain, cytokeratin, lysozyme, glial fibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Because the diagnosis of primary CNS lymphoma ultimately depends on a rigorous postmortem examination to exclude underlying involvement of other organs, 2 the few case reports of primary CNS lymphoma in the veterinary literature are controversial. 3,17,32,37 It is hoped that this rigorous approach will lead to better designed prospective studies to confirm the hypothesis developed from this study that these histological patterns, together with their MRI profiles (Sturges et al, in preparation), accurately reflect targeting of specific anatomical compartments, which is in turn dependent on the expression of different homing molecules among the lymphoma subtypes. Such studies would lead to improved clinical diagnosis and prognosis, better understanding of the molecular pathogenesis, and innovative therapeutic targeting nervous system lymphoma.…”
Section: Discussionsupporting
confidence: 56%
“…Because the diagnosis of primary CNS lymphoma ultimately depends on a rigorous postmortem examination to exclude underlying involvement of other organs, 2 the few case reports of primary CNS lymphoma in the veterinary literature are controversial. 3,17,32,37 It is hoped that this rigorous approach will lead to better designed prospective studies to confirm the hypothesis developed from this study that these histological patterns, together with their MRI profiles (Sturges et al, in preparation), accurately reflect targeting of specific anatomical compartments, which is in turn dependent on the expression of different homing molecules among the lymphoma subtypes. Such studies would lead to improved clinical diagnosis and prognosis, better understanding of the molecular pathogenesis, and innovative therapeutic targeting nervous system lymphoma.…”
Section: Discussionsupporting
confidence: 56%
“…Positive CD79α labelling was observed in all evaluated canine and feline tumours, what was also confirmed in other research (Webb et al 2008, Van Wettere et al 2009). However, Moore et al revealed, that about 20% of EMPs are CD79α-negative (Moore et al 2000).…”
Section: Discussionsupporting
confidence: 89%
“…The predisposed locations in dogs are pinnae, digits, and oral cavity (Van Wettere et al 2009, Gupta et al 2014. In dogs, malignancy of the neoplasm depends on the primary lesion localization.…”
Section: Introductionmentioning
confidence: 99%
“…However, extramedullary plasma cell tumors are extremely rare in the brain of humans (Ferrari et al 2012) and animals. Two cases of primary extramedullary plasma cell tumors in the brain have been reported in dogs (Sheppard et al 1997; Van Wettere et al 2009). To the author’s knowledge, no cases of primary extramedullary plasma cell tumor in the brain of rats or mice have been published.…”
Section: Maybe Not a No-brainermentioning
confidence: 99%